Sistem Pakar Mendeteksi Kerusakan Sepeda Motor Menggunakan Metode Naïve Bayes di Bengkel Motor SMK Islam Tanjung - Na Sa I; Nindian Puspa Dewi (Insand Comtech : Information Science and Computer Technology Journal, 2020)
Expert systems are systems or programs that behave as experts. Expert systems are knowledge-based systems that can be used to help solve problems that exist in the real world. Naive Bayes is a simple probabilistic classification that calculates a set of probabilities by adding up frequencies and combinations of values from a dataset, so Naïve bayes can be used as a method in expert system applications to determine the probability of a damage that may occur on a motorcycle. in this study, an expert system application was created that could detect motorcycle damage and was able to provide solutions such as an expert at Islamic Vocational High School  Tanjung motorcycle repair shop that built  by using the php programming language.